Endometriosis of triple localisation: rectovaginal septum, post-caesarean scar and ovary - Kalandyk-Osinko, Katarzyna; Pas, Katarzyna; Skręt-Magierło, Joanna; Kaznowska, Ewa; Skręt, Andrzej (Menopause Review/Przegląd Menopauzalny, 2011)
The authors discuss the symptoms, pathogenesis and treatment of endometriosis of multiple localization: in the recto-vaginal septum, in a post-caesarean scar and in the ovary. In the available literature we found no data on the prevalence of endometriosis in triple localisation. The authors discuss symptoms, pathogenesis and treatment of endometriosis concerning the described localisation.